STRATEGI PEMERINTAH KOTA PROBOLINGGO DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA PROBOLINGGO - Husni Mubaroq; Rahma Wati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Human Resources or HR has an important role in the process of administering government, both at the Central and Regional levels. Human Resources, which includes all the potential or abilities that exist in humans, both physical and non-physical potential. HR in the context of an agency or institution concerns the employees or workers in an agency. Civil Servant is a person who has fulfilled certain requirements that have been determined by the agency in accordance with the law. One of them is a Civil Servant at the Probolinggo City Personnel and Human Resources Development Agency. BKPSDM itself is an abbreviation of the Agency for Personnel and Human Resources Development which is in charge of or functions as an agency or agency that handles personnel and human resource development. To form professional and humility human resources, especially Civil Servants in the BKPSDM, it is necessary to develop strategies made or carried out by the Probolinggo City Government in improving human resources in the Probolinggo City Personnel and Human Resources Development Agency. Based on the observations of researchers about the Probolinggo City Government Strategy in Improving Human Resources at the Probolinggo City Personnel and Human Resources Development Agency, the results of this study are in accordance with the programs or activities carried out by the Probolinggo City Government as a strategy to increase human resources in the Personnel and Development Agency. Probolinggo City Human Resources